Synthesis, Characterization and Biological Evaluation of Metal(II) Complexes Containing Triphenylphosphine and Schiff Base Ligand Based on 3-Methoxysalicylaldehyde - Gokulnath, G.; Anitha, P.; Manikandan, R.; Umarani, C. (Asian Journal of Chemistry, 2021)
Schiff base ligand (HL) derived from condensation of 3-methoxy salicylaldehyde with 4-aminobenzoic acid and its metal(II) complexes containing triphenylphosphine of the type [MCl(PPh3)(L)] (M = Ni2+, Co2+ or Cu2+; L = bitendate Schiff base ligand) have been synthesized. All the metal(II) complexes were characterized by analytical and spectroscopic (FT-IR, electronic, ESI-Mass, ESR, 1H, 13C NMR and 31P NMR) techniques. All the synthesized compounds were evaluated for in vitro antimicrobial efficiency against Gram-positive bacteria, Gram-negative bacteria and fungai using the agar well diffusion method. Anticancer activity in vitro of the ligand and its metal(II) complexes were also screened against MCF-7 cancer cell lines (human breast cancer cell line).